The efficiency of plasma coatings under fretting-corrosion - Хімко, А.М. (Proceedings of National Aviation University (archive), 2007)
The regions of workability, where have take place the change of mechanisms of wear, of the plasma coverages ВКНА, ПГ10Н-01, ПС12НВК-01 and molybdenum are determine. Three characteristic regions for coverages are shown: normal wearability, moderate wearability and region of inadmissible conditions of exploitation. It is set, that coverage of molybdenum showed the best results on wearability. This coverage has the widest range of normal wearability and the least range of inadmissible conditions of exploitation, that allows it to use in the enough wide terms of loading.